Anticoagulation Therapy - Basaran, Ozcan; Biteker, Murat (IntechOpen, 2016)
The available parenteral and oral anticoagulants have a large clinical use. Understanding biochemistry of anticoagulants may help to improve therapeutic strategies. Resistance to vitamin K antagonist drugs might be a problem for rodent populations. Patients who have thrombogenic risk factors should be anticoagulated. The need for cardiac implantable electronic devices is increasing, and there is a substantial number of patients who are on oral anticoagulant therapy. Prothrombin complex concentrate and other plasma concentrates are useful to deal with over-coagulated situations. The efficacy and safety of non-vitamin K antagonist oral anticoagulants have been proven in large phase III trials. The real-world data suggest even better outcomes with these agents compared to vitamin K antagonists.